Local- and regional-scale air pollution modelling (PM10) and exposure assessment for pregnancy trimesters, infancy, and childhood to age 15 years: Avon Longitudinal Study of Parents And Children (ALSPAC). (April 2018) - Gulliver, John; Elliott, Paul; Henderson, John; Hansell, Anna L.; Vienneau, Danielle; Cai, Yutong; McCrea, Adrienne; Garwood, Kevin; Boyd, Andy; Neal, Lucy; Agnew, Paul; Fecht, Daniela; et al.
Abstract: We established air pollution modelling to study particle (PM10 ) exposures during pregnancy and infancy (1990–1993) through childhood and adolescence up to age ~15 years (1991–2008) for the Avon Longitudinal Study of Parents And Children (ALSPAC) birth cohort. For pregnancy trimesters and infancy (birth to 6 months; 7 to 12 months) we used local (ADMS-Urban) and regional/long-range (NAME-III) air pollution models, with a model constant for local, non-anthropogenic sources. For longer exposure periods (annually and the average of birth to age ~8 and to age ~15 years to coincide with relevant follow-up clinics) we assessed spatial contrasts in local sources of PM10 with a yearly-varying concentration for all background sources. We modelled PM10 (μg/m 3 ) for 36, 986 address locations over 19 years and then accounted for changes in address in calculating exposures for different periods: trimesters/infancy (n = 11, 929); each year of life to age ~15 (n = 10, 383). Intra-subject exposure contrasts were largest between pregnancy trimesters (5 th to 95 th centile: 24.4–37.3 μg/m 3 ) and mostly related to temporal variability in regional/long-range PM10 . PM10 exposures fell on average by 11.6 μg/m 3 from first year of life (mean concentration = 31.2 μg/m 3 ) to age ~15 (mean = 19.6 μg/m 3 ), and 5.4 μg/m 3 between follow-up clinics (age ~8 to age ~15). Spatial contrasts in 8-year average PM10 exposures (5 th to 95 th centile) were relatively low: 25.4–30.0 μg/m 3 to age ~8 years and 20.7–23.9 μg/m 3 from age ~8 to age ~15 years. The contribution of local sources to total PM10 was 18.5%–19.5% during pregnancy and infancy, and 14.4%–17.0% for periods leading up to follow-up clinics. Main roads within the study area contributed on average ~3.0% to total PM10 exposures in all periods; 9.5% of address locations were within 50 m of a main road. Exposure estimates will be used in a number of planned epidemiological studies. Graphical abstract: Unlabelled Image Highlights: PM10 exposure assessment for a large birth cohort (pregnancy, infancy, childhood) Separate exposures for local (main roads, other) and regional/long-range sources. Primary PM10 from local major roads on average was 3% of total PM10 exposures. Largest contrasts for pregnancy trimesters (5 th to 95 th centile: 24.4–37.3 μg/m 3 ) Mean PM10 exposures fell from 31.2 μg/m 3 age ~1 to 19.6 μg/m 3 age ~15 years.